1998
DOI: 10.1001/archneur.55.3.315
|View full text |Cite
|
Sign up to set email alerts
|

All-trans Retinoic Acid Potentiates the Ability of Interferon Beta-1b to Augment Suppressor Cell Function in Multiple Sclerosis

Abstract: Treatment with interferon beta-1b partially restores defective T suppressor cell function in patients with MS. This potentially beneficial action is synergistically potentiated by RA. Interferon beta-1b increases the number of interferon gamma-secreting cells in the circulation when treatment is initiated. A similar increment in interferon gamma-secreting cells is observed when interferon beta-1b is added to cultural peripheral blood mononuclear cells in vitro. This potentially deleterious action of interferon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 42 publications
0
19
1
Order By: Relevance
“…In the longitudinal study, the use of interferon-β did not influence our results. In studies by others on this topic conflicting results have been found: some found a synergistic effect of RA with interferon-β on T suppressor cell augmentation (Qu et al, 1998), others found the association between vitamin A and MRI outcomes to be non-significant during interferon-β use (Loken-Amsrud et al, 2012). We were unable to confirm any of this here.…”
Section: Discussioncontrasting
confidence: 72%
“…In the longitudinal study, the use of interferon-β did not influence our results. In studies by others on this topic conflicting results have been found: some found a synergistic effect of RA with interferon-β on T suppressor cell augmentation (Qu et al, 1998), others found the association between vitamin A and MRI outcomes to be non-significant during interferon-β use (Loken-Amsrud et al, 2012). We were unable to confirm any of this here.…”
Section: Discussioncontrasting
confidence: 72%
“…Cyokine receptor antagonists Anti-IL-12/IL-23p40, IL-1RA, lenercept No (worsening with lenercept, no effect with the others (Constantinescu et al, 1998;Chen et al, 2006;Furlan et al, 2007;Martin and Near, 1995) Targeting/depleting immune cells other than T cells Macrophage/microglia depletion Chlodronate No (Huitinga et al, 1990;Jung et al, 1993;Tran et al, 1998) B cell depletion/blockade AntiCD20/CD19 antibodies Yes (promising) (Hauser et al, 2008;Matsushita et al, 2008;Kap et al, 2010b) Yes (small study plus IFN) (Massacesi et al, 1991;Vergelli et al, 1997;Qu et al, 1998) (Sewell et al, 2002Sewell et al, 2003;Correale and Farez, 2009) (Karussis et al, 1992;Burt et al, 1998;van Bekkum, 2000;Burt et al, 2009;Muraro and Uccelli, 2010;Pasquini et al, 2010) Cell trafficking/based approaches Targeting adhesion molecules required...…”
Section: Anti-cytokine Monoclonal Antibodiesmentioning
confidence: 99%
“…NK cells were enriched with anti-CD3 and anti-CD19 to deplete B cells. (30) B and NK cell purities were .85% based on CD19 or CD56 staining.…”
Section: Isolation Of Mnc and Enrichment For Mnc Subsetsmentioning
confidence: 99%
“…(26) IFNs regulate production of IL-10. In vitro, IFN-b induces small amounts of IL-10 in resting monocytes and mononuclear cells (MNC) (27)(28)(29)(30) and enhances IL-10 secretion is activated T cells. (31,32) In vivo, IFN-b therapy elevates IL-10 mRNA and Department of Neurology, The University of Chicago, Chicago, IL 60637. protein in circulating MNC (29,33,34) and in serum.…”
Section: Introductionmentioning
confidence: 99%